Cultural evolution : the empirical and theoretical landscape - McCaffree, Kevin J. (London Routledge, 2022)
"This book illustrates how fusion-fission cycles actually constitute what we call "culture." Providing specific case studies, including cultural shifts in the 1960s, recurring "moral panics", and nation-formation, the book concludes with general principles of fusion-fission dynamics to help scholars understand this universal phenomenon"--
Includes bibliographical references and index.
Keywords: Social evolution; Culture